NAVIGASI EPISTEMOLOGIS DAN BATAS OPERASIONAL VARIAN FENOMENOLOGI DALAM RISET PENDIDIKAN AGAMA ISLAM - Rifqi Khairul Anam; Wahyudi; Nico; Andi Antoro (Darussalam, 2026)
This study aims to critically examine the epistemological navigation and operational boundaries of various phenomenological variants in Islamic Religious Education (PAI) research. The main issue raised is the tendency to reduce phenomenology to merely a data collection technique, without a deep understanding of its philosophical foundations. This study employs a qualitative approach based on conceptual analysis and literature review of classical and contemporary phenomenological thought. The findings indicate that many studies experience methodological inconsistencies due to the mixing of descriptive (transcendental) phenomenology and hermeneutic phenomenology without full epistemological awareness. In addition, key concepts such as epoché, intentionality, and lived experience are often not properly operationalized in research practice. This study emphasizes the importance of clarity in philosophical positioning when selecting a phenomenological variant, as well as the need to transform research instruments to align with the ontological and epistemological principles of phenomenology. Thus, phenomenological research in PAI is expected to produce more in-depth, authentic analyses with strong methodological validity. Qualitative research with a phenomenological approach is one of the most fundamental methodologies in the social sciences and humanities. This paper comprehensively examines the philosophical foundations, methodological principles, and practical implementation of phenomenological research, ranging from Edmund Husserl’s descriptive phenomenology to Martin Heidegger’s hermeneutic phenomenology, as well as contemporary developments such as Interpretative Phenomenological Analysis (IPA). In addition, this paper reviews the application of phenomenology in various fields such as health, education, and social sciences, accompanied by a critical discussion of the strengths, limitations, and ethical considerations in phenomenological research.